Ethnobotany of Indigofera Cassioides Rottler Ex DC. - Singh, Harish; Srivastava, S. C.; Krishna, G.; Kumar, A. (Indian Forester, 2009)
The present paper provides botanical description, phenology, vernacular names, ecology and distribution along with less known edible, medicinal and other uses of Indigofera cassioides Rottler ex DC. in different parts of India on the basis of field and literature study. This paper also provides method of cultivation of the plant in the waste/barren land as a subsidiary food crop and for the economic benefits of the tribal people.